Hubungan Perilaku Bullying Dengan Tingkat Stres Pada Siswa Kelas 5 Dan 6 Di SDS Pelangi Medan - Ndruru, Rosdian; Simanullang, Rostime Hermayerni (Indonesian Trust Nursing Journal, 2025)
Indonesia is among the countries with the highest reported cases of bullying amongstudents. This phenomenon often occurs in the school environment and has a significantnegative impact on child development, including increasing stress levels. The objective ofthis study is to determine the relationship between bullying behavior and stress levels in 5thand 6th grade students at SDS Pelangi Medan. Research method is Quantitative withanalytic descriptive design with cross sectional survey. The sampling technique usedpurposive sampling. Pearson correlation test was used to analyze the data in this study.The results of this study indicate that there is a relationship between bullying behavior andstress levels in 5th and 6th grade students at SDS Pelangi Medan with a p value = .000 orp <0.005. It is concluded that there is a significant relationship between bullying behaviorand stress levels, schools are expected to provide a deeper understanding of the impact ofbullying on students' mental health and as well as make efforts to prevent and handlebullying cases to reduce stress levels among students. It is suggested for future researchersshould include a larger and more diverse sample of students, and consider the perspectivesof teachers and parents, as well as variables such as social support, academics, and familybackground to understand the relationship between bullying and stress